2016
DOI: 10.3847/0004-637x/824/2/93
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Initiation of the 2006 December 13 Coronal Mass Ejection in Ar 10930: The Structure and Dynamics of the Erupting Flux Rope

Abstract: We carry out a 3D magnetohydrodynamic simulation to model the initiation of the coronal mass ejection (CME) on 2006 December 13 in the emerging δ-sunspot active region NOAA 10930. The setup of the simulation is similar to a previous simulation by Fan, but with a significantly widened simulation domain to accommodate the wide CME. The simulation shows that the CME can result from the emergence of a east-west oriented twisted flux rope whose positive, following emerging pole corresponds to the observed positive … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 25 publications
0
33
1
Order By: Relevance
“…Emerging flux, possibly evolving into flux rope formation, is thought to play a crucial role in supplying free magnetic energy into the AR corona as an energy source for flares and coronal mass ejections (e.g. Fan, 2005;Kazachenko et al, 2015;Fan, 2016), as well as in triggering these events (e.g. Chen and Shibata, 2000;Kusano et al, 2012;Park et al, 2013;Ding, 2015, 2016).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Emerging flux, possibly evolving into flux rope formation, is thought to play a crucial role in supplying free magnetic energy into the AR corona as an energy source for flares and coronal mass ejections (e.g. Fan, 2005;Kazachenko et al, 2015;Fan, 2016), as well as in triggering these events (e.g. Chen and Shibata, 2000;Kusano et al, 2012;Park et al, 2013;Ding, 2015, 2016).…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Specifically, out-of-equilibrium flux ropes, due to their immediate expansion, may not well reproduce the frequently observed, B z -relevant rotation of CMEs about their rise direction (e.g., Démoulin 2008; Thompson et al 2012). This is particularly true for cases in which most of the rotation occurs low in the corona, while the ejected flux is still accelerating (e.g., Török et al 2010;Kliem et al 2012;Fan 2016). Furthermore, inserting a flux rope into a background corona inevitably triggers an unphysical, wave-like perturbation of the system, which superimposes with the modeled CME if the latter starts immediately.…”
Section: Introductionmentioning
confidence: 94%
“…Starting from analytical flux-rope models, Fan and Gibson (2004) and Török and Kliem (2005) reported similarly large rotations (up to 120°) as a result of the same instability. Using a similar flux-rope model, Fan (2016) obtained an even larger rotation of almost 180°, i.e., a full reversal of the magnetic field vector at the front of the flux rope, in a recent simulation of the 13 December 2006 event. Isenberg and Forbes (2007) suggested that the presence of an external shear field surrounding a pre-eruptive flux rope (i.e., of an ambient field component pointing along the axis of the rope) provides a different mechanism for the rotation of a flux rope, once the rope leaves its equilibrium state and rises in the corona.…”
Section: Cme Rotationmentioning
confidence: 99%
“…Many models use observed magnetograms as boundary condition for the magnetic field at the lower boundary, and recently observed surface flows have been included as well (Jiang et al 2016). Some simulations restrict the calculation to the evolution in the corona (e.g., Zuccarello et al 2012b;Amari et al 2014;Fan 2016), while others model the propagation of the ejecta to 1 AU but do not include the coronal evolution. Instead, the latter models start the simulation in the inner heliosphere (typically at around 20-30 R ) and use for the initial ICME some idealized model whose parameters are chosen guided by coronagraph observations (e.g., Shiota and Kataoka 2016).…”
Section: Modeling Cmes From Sun To Earth: the Bastille Day Eventmentioning
confidence: 99%